A layered (n-C4H9NH3)2CsAgBiBr7 perovskite for bipolar resistive switching memory with a high ON/OFF ratio. Issue 29 (21st July 2021) - Kim, So-Yeon; Yang, June-Mo; Lee, Sun-Ho; Park, Nam-Gyu
Abstract : Reduction of dimensionality of a lead-free perovskite from 3D to 2D improves the ON/OFF ratio from 10 2 to 10 7 . Abstract : Lead-based halide perovskites have been proposed as potential candidates for resistive switching memristors due to the high ON/OFF ratio along with millivolt-level low operational voltage. However, lead-free perovskites with 3-dimensional structures, such as Cs2 AgBiBr6, were reported to suffer from low ON/OFF ratios. We report here that reduction of dimensionality is an effective method to improve remarkably the ON/OFF ratio in lead-free perovskites. Introduction of butylammonium (BA) into the double perovskite Cs2 AgBiBr6 forms 2-dimensional BA2 CsAgBiBr7, which is confirmed by the well-developed (00 l ) peaks from powder X-ray diffraction. A 230 nm thick BA2 CsAgBiBr7 film is sandwiched in between Ag and Pt electrodes, which demonstrates bipolar resistive switching behavior with a potential ON/OFF ratio up to 10 7 . Reliable and reproducible SET and RESET processes occur at +0.13 V and −0.20 V, respectively. Endurance of 1000 cycles and a retention time of 2 × 10 4 s are measured. Multi-level storage capability is confirmed by controlling the compliance current. Schottky conduction at the high resistance state (HRS) and ohmic conduction at the low resistance state (LRS) are found to be responsible for resistive switching. The stability test at 85 °C or for 22 days under ambient conditions indicates that BA2 CsAgBiBr7 is durably operable.